FERMI-LAT OBSERVATIONS OF THE GEMINGA PULSAR - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastier, D.; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bignami, G. F.; et al. (Astrophysical Journal, 2010)
We report on the Fermi-LAT observations of the Geminga pulsar, the second brightest non-variable GeV source in the gamma-ray sky and the first example of a radio-quiet gamma-ray pulsar. The observations cover one year, from the launch of the Fermi satellite through 2009 June 15. A data sample of over 60,000 photons enabled us to build a timing solution based solely on gamma-rays. Timing analysis shows two prominent peaks, separated by Delta phi = 0.497 +/- 0.004 in phase, which narrow with increasing energy. Pulsed gamma-rays are observed beyond 18 GeV, precluding emission below 2.7 stellar radii because of magnetic absorption. The phase-averaged spectrum was fitted with a power law with exponential cutoff of spectral index Gamma = (1.30 +/- 0.01 +/- 0.04), cutoff energy E-0 = (2.46 +/- 0.04 +/- 0.17) GeV, and an integral photon flux above 0.1 GeV of (4.14 +/- 0.02 +/- 0.32) x 10(-6) cm(-2) s(-1). The first uncertainties are statistical and the second ones are systematic. The phase-resolved spectroscopy shows a clear evolution of the spectral parameters, with the spectral index reaching a minimum value just before the leading peak and the cutoff energy having maxima around the peaks. The phase-resolved spectroscopy reveals that pulsar emission is present at all rotational phases. The spectral shape, broad pulse profile, and maximum photon energy favor the outer magnetospheric emission scenarios.
CRIS-Team WoS Importer:2020-01-15